Retrospective analysis of SARS-CoV-2 RNA detection in pooled saliva samples: An effective cost-saving method - Charoenkupt, Jiraphat; Burassakarn, Ati; Chaiwongkot, Arkom (Chulalongkorn Medical Journal, 2024)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a causative agent of coronavirus disease 2019 (COVID-19), which was first reported in December 2019 and has since spread globally. Effective laboratory testing is crucial for the early detection and prevention of SARS-CoV-2 trans mission. The use of pooled saliva samples represents a potential method for active case finding and increasing testing efficiency. Objectives: To evaluate the effectiveness of pooled saliva samples for SARS-CoV-2 testing and its costeffectiveness for screening healthcare workers at King Chulalongkorn Memorial Hospital, Thai Red Cross Society. Methods: A total of 24,098 samples collected between April 19, 2021, and May 30, 2022, to be tested for the presence of SARS-CoV-2 were analyzed retrospectively. The samples were examined individually and in pools of four and six using the Cobas 6,800 reverse-transcription polymerase chain reaction assay for the detection of SARS-CoV-2 RNAs. The analysis focused on changes in cycle threshold values for each target between positive pools and positive individual samples. Results: SARS-CoV-2 was detected in 0.5% of the samples (123/24,098). Pooling saliva samples in groups of four or six did not compromise the detection of viral RNAs. Pooled saliva testing showed high performance for SARS-CoV-2 detection, with cost reductions of 73.5% for the four-sample pools and 80.7% for the sixsample pools compared with individual testing. Conclusion: Pooling saliva samples is a cost-effective and efficient method for screening SARS-CoV-2, particularly in low-prevalence settings. This approach helps quickly identify and isolate healthcare workers with infection, thus reducing transmission and preserving resources.